FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS AGROINDUSTRI GULA KELAPA DI KABUPATEN PANGANDARAN - Ane Novianty; Benidzar M. Andrie (Universitas Galuh Ciamis, 2020)
The study was conducted with the aim to find out the factors that influence the profitability of coconut sugar agroindustry in Pangandaran District. The study used a survey of 100 coconut sugar crafters taken from 10 districts in Pangandaran District. Factors that affect profitability are analyzed using multiple linear regression. The results showed that the profitability achieved by coconut sugar agro-industry in Pangandaran Regency was 12.93, which showed that the coconut sugar agro-industry was profitable. Capital and production partially have a significant effect on the profitability of coconut sugar agro-industry, while labor and raw materials have no significant effect.